Fracture resistance of weakened teeth restored with condensable resin with and without cusp coverage (Journal of Applied Oral Science, 2009)
OBJECTIVES: This in vitro study evaluated the fracture resistance of weakened human premolars (MOD cavity preparation and pulp chamber roof removal) restored with condensable resin composite with and without cusp coverage. MATERIAL AND METHODS: Thirty human maxillary premolars were divided into three groups: Group A (control), sound teeth; Group B, wide MOD cavities prepared and the pulp chamber roof removed and restored with resin composite without cusp coverage; Group C, same as Group B with 2.0 mm of buccal and palatal cusps reduced and restored with the same resin. The teeth were included in metal rings with self-curing acrylic resin, stored in water for 24 h and thereafter subjected to a compressive axial load in a universal testing machine at 0.5 mm/min. RESULTS: The mean fracture resistance values ± standart deviation (kgf) were: group A: 151.40 ± 55.32, group B: 60.54 ± 12.61, group C: 141.90 ± 30.82. Statistically significant differences were found only between Group B and the other groups (p